The Development of Authentic English Learning Materials for a Marine Hotel Course - Soraya, Kiky (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2024)
Framed in Design Based Research (DBR), the authors investigated the target needs and learning needs of the students in developing their English skills at a Marine Hotel Course Institution in Indonesia and developed the appropriate English learning materials for the students. The subjects of the research were 14 students of a Marine Hotel Course Institution in Indonesia. The instruments used in this study were Questionnaires, Field Notes, and Interview Guidelines. The data of this research were analyzed quantitatively and qualitatively. The research findings show that the appropriate English learning materials for the students should be Authentic and consist of three parts: Introduction, Main Activities, and Reinforcement. It shows that the appropriate tasks for the students have six components: goals, input, activity, setting, student role, and teacher role. Based on the research findings, each unit consists of two cycles i.e. oral cycle for listening and speaking skills and written cycle for reading and writing skills. The materials provide language function in the oral cycle, grammar in the written cycle, and pronunciation and vocabulary lessons in both cycles. From the results of the materials evaluation, the mean values of the statements were 3.86 to 4.77. Based on the quantitative data conversion from 0-5, those ranges were in the good and very good categories. Those data were supported by the data from the interview and the observation. It can be concluded that the suggested materials were appropriate and the students were satisfied in using the designed materials.